Multiple oncogenic mutations related to targeted therapy in nasopharyngeal carcinoma - Zhang, Jian‐Wei; Qin, Tao; Hong, Shao‐Dong; Zhang, Jing; Fang, Wen‐Feng; Zhao, Yuan‐Yuan; Yang, Yun‐Peng; Xue, Cong; Huang, Yan; Zhao, Hong‐Yuan; Ma, Yu‐Xiang; Hu, Zhi‐Huang; et al. (Ai zheng, 2015)
Introduction： An increasing number of targeted drugs have been tested for the treatment of nasopharyngeal carcinoma （NPC）. However, targeted therapy-related oncogenic mutations have not been fully evaluated. This study aimed to detect targeted therapy-related oncogenic mutations in NPC and to determine which targeted therapy might be potentially effective in treating NPC. Methods： By using the SNaPshot assay, a rapid detection method, 19 mutation hotspots in 6 targeted therapy-related oncogenes were examined in 70 NPC patients. The associations between oncogenic mutations and clinicopathologic factors were analyzed. Results： Among 70 patients, 12 （1 7.1%） had mutations in 5 oncogenes： 7 （10.0%） had v-kit Hardy-Zuckerman 4 feline sarcoma viral oncogene homolog （KIT） mutation, 2 （2.8%） had epidermal growth factor receptor （EGFR） mutation, 1 （1.4%） had phosphatidylinositol-4,5-bisphosphate 3-kinase, catalytic subunit alpha （PIK3CA） mutation, 1 （IA%） had Kirsten rat sarcoma viral oncogene homolog （KRAS） mutation, and 1（1.4%） had simultaneous EGFB and v-Raf murine sarcoma viral oncogene homolog BI （BRAF） mutations. No significant differences were observed between oncogenic mutations and clinicopathologic characteristics. Additionally, these oncogenic mutations were not associated with tumor recurrence or metastasis. Conclusions： Oncogenic mutations are present in NPC patients. The efficacy of targeted drugs on patients with the related oncogenic mutations requires further validation.